Methodical instructions for the course project "Economic evaluation of product manufacturing at the enterprise" - Havrys, O. O.; Havrys, M. O.; Havrys, O. M. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The economic evaluation of production at industrial enterprises is an important task that can be solved by carrying out research, design and technological works. The course project evaluates potential sales markets for products, calculates the cost of production, determines the cost of production assets and the amount of depreciation deductions. The values of labor and salary indicators and indicators of the efficiency of the use of production assets are also calculated. When conducting calculations, potential risks and their impact on the level of economic indicators are assessed. A possible financing strategy is evaluated, credit indicators are calculated. A number of sections of the executive course project are drawn up according to the business plan development method. In general, the essence of the work consists in the comparison of two products that can potentially be produced at the enterprise (basic product and new product). All the calculations described above are made for both basic and new products. The goal is to determine which product is more expedient to manufacture at the enterprise and why. The introduction to the course project briefly describes the content of the development and the main tasks to be solved (the student must formulate the content and tasks of his work). Most calculations are done in tables. At the end of the work, there should be a small conclusion in which the results of the calculations are evaluated and the choice of one or another product for production at the enterprise is justified.
Keywords: methodical instructions; product description; evaluation of the sales market; financial plan; calculation; economic activity